2018
DOI: 10.1111/bph.14099
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous use of erythropoietin and LFM‐A13 as a new therapeutic approach for colorectal cancer

Abstract: Background and PurposeBruton's tyrosine kinase (Btk) is a non‐receptor tyrosine kinase involved in the activation of signalling pathways responsible for cell maturation and viability. Btk has previously been reported to be overexpressed in colon cancers. This kind of cancer is often accompanied by anaemia, which is treated with an erythropoietin supplement. The goal of the present study was to assess the effects of combination therapy with erythropoietin β (Epo) and LFM‐A13 (Btk inhibitor) on colon cancer in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
2
15
0
1
Order By: Relevance
“…In this study, we not only confirmed the antiproliferative action of LFM-13 in both breast cancer cells lines but also indicated that the addition of Epo to this system further reduced viability of these cells. These results are consistent with our previous findings, which demonstrated that Epo appears to be a chemosensitizer and showed a synergistic antiproliferative effect with LFM-A13 in two colon cancer cells DLD-1 and HT-29 23 . The high effectiveness of the combination used has also been confirmed in zebrafish embryo xenograft model.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we not only confirmed the antiproliferative action of LFM-13 in both breast cancer cells lines but also indicated that the addition of Epo to this system further reduced viability of these cells. These results are consistent with our previous findings, which demonstrated that Epo appears to be a chemosensitizer and showed a synergistic antiproliferative effect with LFM-A13 in two colon cancer cells DLD-1 and HT-29 23 . The high effectiveness of the combination used has also been confirmed in zebrafish embryo xenograft model.…”
Section: Discussionsupporting
confidence: 94%
“…The fish were incubated with Epo þ LFM-A13 at the highest doses for 48 h. The control group received the solvent LFM-A13 (10% DMSO/PBS). In both MCF-7 and MDA-MB- 23 xenografts we observed significant reduction in tumour development in Epo þ LFM-A13 treated group compared with the control (Figure 1(F)). As shown in Figure 1(G 13 .…”
Section: Erythropoietin With Lfm-a13 Decrease Cell Proliferation and mentioning
confidence: 80%
See 1 more Smart Citation
“…Animal studies are reported in compliance with the ARRIVE guidelines [ 47 ]. Xenograft animal models were obtained as described previously [ 14 ] using DLD-1 and HT-29 cells (50 μL suspension containing 1 × 10 8 cells for each animal, Figure 5 a). In previous studies, we showed no effect of the Epo solvent on the number of colon cancer cells [ 20 ] and, in accordance with the 3R, we reduced the number of animals [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that Epo used to treat anemia promotes survival, proliferation, and differentiation of the progenitors of erythropoiesis, exerting a proangiogenic and antiapoptotic effect [ 12 , 13 ]. Despite this, the results of our recent study indicate that Epo intensifies the antiproliferative activity of LFM-A13 [ 14 ].…”
Section: Introductionmentioning
confidence: 92%